The Effect of Bandwagon Effect on Clothing Consumption Patterns (Study on Muslim Community in Tanete Riattang Sub-District) - Tama, Megawati Reski; Zulkifli, Zulkifli; Munawarah, Munawarah (Jurnal Ekonomi dan Perbankan Syariah, 2024)
Humans carry out consumption activities to meet their needs. There are two types of behavior in consumers, namely rational and irrational consumer behavior. This research aims to determine the effect of bandwagon effect on clothing consumption patterns in Muslim communities in Tanete Riattang District. The research method used is quantitative. The data collection technique was carried out by giving questionnaires to 100 respondents. The analysis technique carried out is a statistical test through a simple linear regression test, t test, and coefficient of determination (R2). Before statistical tests are carried out, research instrument tests are carried out, namely validity tests, reliability tests, and classical assumption tests consisting of normality tests and linearity tests. Data management in this study used SPPS 29 software. The results showed that the bandwagon effect had a positive and significant effect on clothing consumption patterns in the Muslim community in Tanete Riattang sub-district. Based on the results of the t test, it is known that t_value (8.275) t_table (1.984) and the significance value of 0.000 is smaller than the established probability ꭤ which is 0.05 which means that a person's clothing consumption pattern is based on a tendency to buy or recognize trends because many other people also do it.